meso-1-{[2-(Propyl-1-sulfinyl)ethyl]sulfinyl}propane - Wardell, S.M.S.V.; Wardell, J.L.; de Lima, G.M.; Tiekink, E.R.T. (International Union of Crystallography, 2010)
The title molecule, C8H18O2S2, is disposed about a centre of inversion implying an anti-disposition of the sulfinyl-O atoms; the terminal n-propyl group has an extended conformation. The crystal packing is dominated by C-H center dot center dot center dot O interactions, which lead to the formation of supramolecular arrays in the bc plane.